2019
DOI: 10.1080/21679169.2019.1650394
|View full text |Cite
|
Sign up to set email alerts
|

See me, teach me, guide me, but it’s up to me! Patients’ experiences of recovery during the acute phase after hip fracture

Abstract: Aim: To explore patients' experiences of their recovery after hip fracture surgery and the use of Traffic Light System-BasicADL in their rehabilitation process. Method: Nineteen patients (13 females and 6 males), aged 66-94, were interviewed. A qualitative content analysis method was used for analysis of data. Results: Two categories were identified: 'Being seen as a person' with subcategories; Interaction affects trust and security; Information is key to understanding; and Encouragement is essential to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Four studies were conducted in the United Kingdom [10,12,29,30], three in Sweden [13,31,32], four in Canada [11,[33][34][35], one in Norway [36], in New Zealand [37], and one in the Netherlands [38]. Two studies were carried out in the hospital setting [10,13], one a rural community setting [31], and the remaining studies in urban community settings [11,12,29,30,[32][33][34][35][36][37][38]. Six studies selected their sample from participants of a randomized control trial [11,13,32,33,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were conducted in the United Kingdom [10,12,29,30], three in Sweden [13,31,32], four in Canada [11,[33][34][35], one in Norway [36], in New Zealand [37], and one in the Netherlands [38]. Two studies were carried out in the hospital setting [10,13], one a rural community setting [31], and the remaining studies in urban community settings [11,12,29,30,[32][33][34][35][36][37][38]. Six studies selected their sample from participants of a randomized control trial [11,13,32,33,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In 2011, a literature review of older adults' recovery from hip fracture suggested patient recovery outcome is influenced by physical function and psychosocial factors [9]. Since this time, there has been an influx of qualitative evidence exploring both patient and carer's perspectives of recovery at different stages after hip fracture [10][11][12][13]. This evidence adds depth to previous understanding of quantitative trajectories for recovery [11,12] as well as patient and carer's perspectives of care received in support of recovery after hip fracture [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since investigating TLS-BasicADL for concurrent validity, two further studies investigating clinical utility and patients experiences of using TLS-BasicADL have been performed [17,35]. In the first study investigating early co-ordinated rehabilitation after hip fracture surgery TLS-BasicADL was used as a tool to communicate with the patient previous and present function and ADL status, and as a visual aid for discussing and updating rehabilitation goals [17].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that patients in the intervention group experienced higher levels of patient participation and reported greater levels of independence in ADL at discharge compared to the control group. A further study has investigated patients experiences of recovery after hip fracture during the acute inpatient phase including the use of TLS-BasicADL [35]. The instrument was described as easy to understand, included appropriate and relevant activities and valued by patients as the protocol highlighted for staff the activities patients required help with.…”
Section: Discussionmentioning
confidence: 99%